Implementasi E-Business Dan Manajemen Strategis Dalam Operasional Gerai : Tinjauan Dari Pengalaman Magang Di PT. Inspirasi Bisnis Nusantara - Muhamad Angga Sangkara; Fathur Rosi (Jurnal Kajian dan Penalaran Ilmu Manajemen, 2026)
The rapid development of information technology has driven the transformation of conventional business models towards digital ones. PT. Inspirasi Bisnis Nusantara, as a business entity engaged in retail and food and beverage, faces challenges in integrating technology into store operations to maintain competitiveness. This article aims to analyze the implementation of e-business and the application of strategic management in the store operations of PT. Inspirasi Bisnis Nusantara. This research uses a descriptive qualitative method with a case study approach, in which data were collected through direct observation, in-depth interviews, and documentation during the internship period. The analysis results show that the implementation of e-business through cloud-based Point of Sales (POS) systems and digital inventory management has successfully improved operational efficiency and data accuracy. Furthermore, the company's strategic management, which focuses on technology-based customer service, proves effective in adapting to changes in consumer behavior. However, challenges related to the readiness of Human Resources (HR) and the stability of internet infrastructure were also found. This article concludes that the synergy between e-business technology and mature strategic planning is the key to the success of store operations in the digital era. : E-Business, Strategic Management, Store Operations, PT. Inspirasi Bisnis Nusantara, Digital Transformation.